Association between reverse electrical remodeling and cardiac fibrosis markers in patients with cardiac resynchronization therapy - Hamza Sunman; Uğur Canpolat; Hikmet Yorgun; Adem Özkan; Muhammet Ulvi Yalçın; Tülin Bayrak; Levent Şahiner; Ergün Barış Kaya; Asuman Özkara; Kudret Aytemir; Ali Oto (KARE Publishing, 2018)
Objective: Cardiac resynchronization therapy (CRT) induces structural and electrical reverse remodeling of the failing heart. However, the association between native QRS narrowing and cardiac fibrosis markers has not been investigated in patients with an implanted CRT device. Methods: A total of 41 symptomatic patients diagnosed with systolic heart failure who underwent CRT implantation were included in this study. Electrocardiogram findings and cardiac fibrosis marker levels [galectin-3, growth-differentiation factor-15 (GDF-15) and procollagen III N-terminal propeptide (P3TD)] were collected before and 12 months after initiation of biventricular pacing. Reverse electrical remodeling was defined as a decrease in 12-month intrinsic QRS (iQRS) duration by ≥20 milliseconds after CRT implantation. Results: The median QRS duration decreased from 155 milliseconds (interquartile range [IQR]: 142-178 milliseconds) before CRT to 142 milliseconds (IQR: 130-161 milliseconds) (p=0.001) after 12 months of CRT. According to the predefined criteria, electrical remodeling was detected in 16 (39.0%) patients. The median galectin-3, GDF-15, and P3TD levels were significantly decreased after CRT implantation in patients with electrical remodeling [27.65 ng/mL (IQR: 24.4-35.2 ng/mL) vs 23.00 ng/mL (IQR: 16.0-36.7 ng/mL), p=0.017; 3104 pg/mL (IQR: 2923-4825 pg/mL) vs 2276 pg/mL (IQR: 1294-3209 pg/mL), p=0.002; 0.43 ng/mL (IQR: 0.23-0.64) vs 0.15 ng/mL (IQR: 0.04-0.29 ng/mL), p=0.034, respectively]. The galectin-3, GDF-15, and P3TD levels were not significantly changed in patients without electrical remodeling [26.80 ng/mL (IQR: 23.9-31.5 ng/mL) vs 28.80 ng/mL (IQR: 23.0-34.8 ng/mL), p=0.211; 4221 pg/mL (IQR: 2709-4995 pg/mL) vs 3035 pg/mL (IQR: 2038-4872 pg/mL), p=0.143; and 0.34 ng/mL (IQR: 0.11-0.68 ng/mL) vs 0.21 ng/mL (IQR: 0.09-0.37 ng/mL), p=0.112, respectively]. Conclusion: The results from the small sample used in this study indicated that electrical reverse remodeling after CRT was associated with a decrease in cardiac fibrosis.